Learning Strategies In The 2013 Curriculum - Rafika Meidiyanti (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Learning activities at every level of education should be developed following current developments, meaning that every teacher must understand learning approaches, strategies, and methods. In the 2013 curriculum, various strategies, models, and learning methods are increasingly varied; as an educator, this is very useful. As a result, educators can be more creative in delivering material. Determining learning strategies at the beginning is essential because a teacher is a primary planner in a learning activity. Educators who are responsible always prepare everything at the beginning of learning to support the learning process so that the atmosphere and results are created as expected. Writing this article aims to explain how important it is to set learning strategies, especially in the 2013 curriculum in the learning process. In writing this article, it uses a qualitative approach using library research, namely by examining reading sources related to the studies discussed. Data was collected by browsing books and scientific journals from Google Scholar, digital libraries, and others.